Anti‐Candida, docking studies, and in vitro metabolism‐mediated cytotoxicity evaluation of Eugenol derivatives. (2nd September 2022) - Dutra, Jessyca Aparecida Paes; Maximino, Sarah Canal; Gonçalves, Rita de Cássia Ribeiro; Morais, Pedro Alves Bezerra; de Lima Silva, William Cezar; Rodrigues, Ricardo Pereira; Neto, Álvaro Cunha; Júnior, Valdemar Lacerda; de Souza Borges, Warley; Kitagawa, Rodrigo Rezende
Abstract: The high morbidity and mortality rates of Candida infections, especially among immunocompromised patients, are related to the increased resistance rate of these species and the limited therapeutic arsenal. In this context, we evaluated the anti‐ Candida potential and the cytotoxic profile of eugenol derivatives. Anti‐ Candida activity was evaluated on C. albicans and C. parapsilosis strains by minimum inhibitory concentration (MIC), scanning electron microscopy (SEM), and molecular docking calculations at the site of the enzyme lanosterol‐14‐α‐demethylase active site, responsible for ergosterol formation. The cytotoxic profile was evaluated in HepG2 cells, in the presence and absence of the metabolizing system (S9 system). The results indicated compounds 1b and 1d as the most active ones. The compounds have anti‐ Candida activity against both strains with MIC ranging from 50 to 100 μg ml −1 . SEM analyses of 1b and 1d indicated changes in the envelope architecture of both C. albicans and C. parapsilosis like the ones of eugenol and fluconazole, respectively. Docking results of the evaluated compounds indicated a similar binding pattern of fluconazole and posaconazole at the lanosterol‐14‐α‐demethylase binding site. In the presence of the S9 system, compound 1b showed the same cytotoxicity profile as fluconazole (1.08 times) and compound 1d had 1.23 times increase in cytotoxicity. Eugenol and other evaluated compounds showed a significant increase in cytotoxicity. Our results suggest compound 1b as a promising starting point candidate to be used in the design of new anti‐ Candida agent prototypes. Abstract : New eugenol derivatives were sintetize and Anti‐ Candida, Docking Studies, and in vitro Metabolism‐mediated Cytotoxicity Evaluation were performed.